2022
DOI: 10.3389/fmicb.2022.868887
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Sequencing and Analysis of a Novel Human Cowpox Virus With Mosaic Sequences From North America and Old World Orthopoxvirus

Abstract: Orthopoxviruses (OPXVs) not only infect their natural hosts, but some OPXVs can also cause disease in humans. Previously, we partially characterized an OPXV isolated from an 18-year-old male living in Northern Norway. Restriction enzyme analysis and partial genome sequencing characterized this virus as an atypical cowpox virus (CPXV), which we named CPXV-No-H2. In this study, we determined the complete genome sequence of CPXV-No-H2 using Illumina and Nanopore sequencing. Our results showed that the whole CPXV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 92 publications
5
27
0
1
Order By: Relevance
“…Poxviruses recombine at a high level under laboratory conditions, and some naturally derived poxvirus recombinants have been isolated from nature. A novel CPXV strain isolated from a Norwegian patient has a mosaic genome that may have arisen out of recombination with three other OPXV species [ 66 ]. Several poxvirus species isolated in this century from human patients, including two novel OPXV species, show evidence of recombination with OPXV [ 5 , 6 ].…”
Section: Poxvirus Evolutionmentioning
confidence: 99%
“…Poxviruses recombine at a high level under laboratory conditions, and some naturally derived poxvirus recombinants have been isolated from nature. A novel CPXV strain isolated from a Norwegian patient has a mosaic genome that may have arisen out of recombination with three other OPXV species [ 66 ]. Several poxvirus species isolated in this century from human patients, including two novel OPXV species, show evidence of recombination with OPXV [ 5 , 6 ].…”
Section: Poxvirus Evolutionmentioning
confidence: 99%
“…At least in lab settings, gene multiplication also seems to be a fairly typical way for poxvirus to adjust to the environment quickly. Drugresistant VACV mutants, such as those resistant to rifampin or hydroxyurea, which inhibit several phases of VACV replication, developed very quickly when these medicines were added during passage [35,36].…”
Section: Evolution Of Poxvirusmentioning
confidence: 99%
“…Many of the mutants have tandem repeats of a viral gene in their genomes that is either the direct drug target or a near companion of the drug target [35,36], enabling them to reduce the medication effect by boosting the gene dosage. Similar to how VACV rapidly extended their genome by copying a viral gene (K3L or a related gene) that encodes a weak human PKR inhibitor, VACV did the same to circumvent the activity of the human antiviral protein PKR [37,38].…”
Section: Evolution Of Poxvirusmentioning
confidence: 99%
“…Regarding the recognition of MPXV, von Manguns et al recorded two epidemics of non-fatal pox-like diseases amongst cynomolgus macaque monkeys transported from Singapore to Denmark in 1958. This isolated and cultured virus which had different molecular characteristics from other known Orthopoxviruses was named MPXV (Diaz-Cánova et al 2022, Kaynarcalidan et al 2021. Controversially, MPXV and VARV were often considered close relatives, although comparative genomics has shown that MPXV was a unique virulent species derived from another orthopoxvirus ancestor.…”
Section: Accepted Manuscriptmentioning
confidence: 99%